Composting for the treatment of cattle wastes - Bujang, K.B.; Lopez-Real, J.M. (Taylor and Francis Group, 1993)
▪ Livestock farming in England and Wales is estimated to produce an annual figure of 200 million tons of animal excreta, half generated by the dairy cattle industry. In the United Kingdom, the structure of the cattle industry has shifted from large numbers of small dairy farms to fewer but larger units. The national average herd size increased from 26 to 42 and finally to 64 animals in 1965, 1975 and 1985, respectively. The latest census revealed that currently there were 2.44 million dairy cows and 9.45 million other cattle and calves in the United Kingdom (total 11.89 million), third place after France (21.50 million) and Germany (19.51 million) in the EEC countries.